2017
DOI: 10.1002/1873-3468.12643
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of SgvP involved in carbon–sulfur bond formation during griseoviridin biosynthesis

Abstract: Coordinate and structure factor were deposited in the Protein Data Bank database under the accession number 4MM0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…30 The role of this natural product or intermediate is not clear, but deletion of the CYP154A1-encoding gene compromised the stability of the bacterial spores of the producing strain. 30 Three additional structures of P450s from Streptomyces , StaF (PDB ID: 5EX8), 106 SgvP (4MM0), 189 and CYP105P2 (5IT1), 190 revealed that their heme groups also adopt this unusual flipped orientation (Fig. 8A).…”
Section: Structurementioning
confidence: 99%
“…30 The role of this natural product or intermediate is not clear, but deletion of the CYP154A1-encoding gene compromised the stability of the bacterial spores of the producing strain. 30 Three additional structures of P450s from Streptomyces , StaF (PDB ID: 5EX8), 106 SgvP (4MM0), 189 and CYP105P2 (5IT1), 190 revealed that their heme groups also adopt this unusual flipped orientation (Fig. 8A).…”
Section: Structurementioning
confidence: 99%
“…184 A P450 (SgvP) has been implicated in the synthesis of this thioether bridge, 185,186 with gene disruption experiments showing the essential nature of this P450 in thioether formation (Fig. 17D).…”
mentioning
confidence: 99%
“…Akink of acid-alcohol pair (D/ E-T/S) in the I-helix is acommon feature in the great majority of P450s,w hich is important for dioxygen activation during the catalytic cycle. [15] However,the semi-conserved D/E near the conserved threonine (T239) is replaced by ab asic lysine residue (K238) in CxnD.A mong the microbial P450s supposed to be responsible for CÀSb ond formation in secondary metabolite biosynthesis,acrystal structure of SgvP in apo form (PDB ID 4MM0) [16] has been determined, which is rather similar to CxnD in overall structure (RSMD of 2.0 for the Ca-atoms,T able S6). Thes uperposition of SgvP and CxnD structures shows that CxnD has an extra B'-helix and acompact B-C loop compared with SgvP,inagreement with alarger cavity to accommodate the macrolactam substrate for SgvP (Figure S37).…”
Section: Resultsmentioning
confidence: 99%